(3cJGH aj CSeGA GdUMGHI QVi Gddg Yfges - (3eMeO Hf MHGf Hf CMeO Hf MHGf Hf eYGP Hf eYHO GdJejej, CHh MGJe GdHSJj, hjbGd dg GHf MHGf,J (B354 (3g` s
(3ChdgG (B:s
(3hHYO bGd CHh MGJe eMeO Hf MHGf MOKfG Yf YeQGf Hf MUjf bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B((3NjQ CeJi GdbQf GdPi HYKJ ajge Ke GdPjf jdhfge s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3GdfSNI HGgJI efYJ ef QDjI GdfgGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B78 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B173s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3eJaQbGJs